2009
DOI: 10.1371/journal.pntd.0000536
|View full text |Cite
|
Sign up to set email alerts
|

Inaccuracy of Enzyme-Linked Immunosorbent Assay Using Soluble and Recombinant Antigens to Detect Asymptomatic Infection by Leishmania infantum

Abstract: BackgroundOne of the most important drawbacks in visceral leishmaniasis (VL) population studies is the difficulty of diagnosing asymptomatic carriers. The aim of this study, conducted in an urban area in the Southeast of Brazil, was to evaluate the performance of serology to identify asymptomatic VL infection in participants selected from a cohort with a two-year follow-up period.MethodologyBlood samples were collected in 2001 from 136 cohort participants (97 positive and 39 negatives, PCR/hybridization carrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
52
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 30 publications
2
52
0
Order By: Relevance
“…22 Our results agree with other investigators who clinically followed up asymptomatic individuals in Brazil who tested seropositive by ELISArK39, and we found that none of them developed the disease. 4,23,24 One aspect to be considered is the observation that, in the first study, the tests presented a specificity ranging from 96% to 100% using subjects from a non-endemic area as a reference. As a consequence, there was a false-positive rate of up to 4%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…22 Our results agree with other investigators who clinically followed up asymptomatic individuals in Brazil who tested seropositive by ELISArK39, and we found that none of them developed the disease. 4,23,24 One aspect to be considered is the observation that, in the first study, the tests presented a specificity ranging from 96% to 100% using subjects from a non-endemic area as a reference. As a consequence, there was a false-positive rate of up to 4%.…”
Section: Discussionmentioning
confidence: 99%
“…4,13,25 The comparison of tests may provide some additional information that contributes to the selection of the serological tests that best discriminates between infected and uninfected subjects. In this respect, ELISA assays, which are easily performed compared with IIFT and MST, would be an interesting option for this diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PCR has shown higher efficacy than that of serological tests in the identification of asymptomatic cases of VL (12). However, this technique also detected positive results for subjects living in areas of endemicity but who did not progress to classic disease.…”
mentioning
confidence: 98%
“…Some investigators suggested a good sensitivity of ELISA using the recombinant K39 antigen (ELISA-rK39) in the diagnosis of cases of active VL but not cases of inapparent infection (9,10). Other studies found asymptomatic subjects with positive ELISA-rK39 results, but follow-up did not reveal progression of these cases to classic VL (11)(12)(13).…”
mentioning
confidence: 99%